Correction to: Tetrahedral Framework Nucleic Acid‑Based Delivery of Resveratrol Alleviates Insulin Resistance: From Innate to Adaptive Immunity - Li, Yanjing; Gao, Shaojingya; Shi, Sirong; Xiao, Dexuan; Peng, Shuanglin; Gao, Yang; Zhu, Ying; Lin, Yunfeng (Nano-Micro Letters, 2021)
Obesity-induced insulin resistance is the hallmark of metabolic syndrome, and chronic, low-grade tissue inflammation links obesity to insulin resistance through the activation of tissue-infiltrating immune cells. Current therapeutic approaches lack efficacy and immunomodulatory capacity. Thus, a new therapeutic approach is needed to prevent chronic inflammation and alleviate insulin resistance. Here, we synthesized a tetrahedral framework nucleic acid (tFNA) nanoparticle that carried resveratrol (RSV) to inhibit tissue inflammation and improve insulin sensitivity in obese mice. The prepared nanoparticles, namely tFNAs-RSV, possessed the characteristics of simple synthesis, stable properties, good water solubility, and superior biocompatibility. The tFNA-based delivery ameliorated the lability of RSV and enhanced its therapeutic efficacy. In high-fat diet (HFD)-fed mice, the administration of tFNAs-RSV ameliorated insulin resistance by alleviating inflammation status. tFNAs-RSV could reverse M1 phenotype macrophages in tissues to M2 phenotype macrophages. As for adaptive immunity, the prepared nanoparticles could repress the activation of Th1 and Th17 and promote Th2 and Treg, leading to the alleviation of insulin resistance. Furthermore, this study is the first to demonstrate that tFNAs, a nucleic acid material, possess immunomodulatory capacity. Collectively, our findings demonstrate that tFNAs-RSV alleviate insulin resistance and ameliorate inflammation in HFD mice, suggesting that nucleic acid materials or nucleic acid-based delivery systems may be a potential agent for the treatment of insulin resistance and obesity-related metabolic diseases. Highlights: 1 Tetrahedral framework nucleic acid (tFNA)-based delivery of resveratrol (RSV) ameliorates the performance of RSV. 2 tFNAs-RSV improve insulin sensitivity in high-fat diet-fed mice by promoting Treg and Th2 and suppressing Th1 and Th17, and switching macrophage from M1 to M2 phenotype both in vitro and in vivo.